Hermia & Helena [videorecording (DVD)] - Piñeiro, Matías, 1982-; Muñoz, Agustina; Villar, María; Diop, Mati, 1982- (Kino Lorber, 2017)
Camila, a young Argentine theater director, travels from Buenos Aires to New York for an artist residency to work on a new Spanish translation of Shakespeare's A Midsummer Night's Dream. Upon her arrival, she quickly realizes that her work isn't compensating for the loss of her friends and the lover she left behind. When she begins to receive a series of mysterious postcards from Danil̈e, Camila second-guesses her artistic endeavors and begins to seek answers about her past.